An easy approach to ultrasonographic volumetry of the thyroid - Tsukasa Murakami; Naoyuki Higaki; Yui Nishijima; Junichi Tani; Hitoshi Noguchi; Manami Morisaki; Misako Eto; Yoshiko Tani (Endocrine Journal)
To establish an easy way to perform volumetry of the thyroid gland using ultrasonography, we evaluated the accuracy of the products of the depth and width of the right thyroid lobe as indices of thyroid volume. The depth and width of both thyroid lobes were measured using ultrasonography before surgery in 193 patients with Graves’ disease. The products were compared with the weight of the thyroid obtained from operative records. We also evaluated the depth and width of the right thyroid lobe in 312 subjects who presented without any thyroid disease. The products of depth and width of the right and left lobes of patients with Graves’ disease correlated similarly well with the weight of the thyroid obtained from operative records (ρ = 0.896 for right, ρ = 0.886 for left, p < 0.0001). Because the right lobes were larger than the left lobes, the products of the depth and width of the right lobe were adopted as novel parameters for an easy volumetric approach. The relationship between the weight and the measurements of the right lobe was described using the following regression equation: weight (g) = [11.8 × depth (cm) × width (cm)] – 16.0. The products of the subjects without any thyroid diseases were distributed between 0.6 cm2 and 4.4 cm2, with a median of 2.0 cm2. The upper limit of these values in these subjects was estimated to be 3.8 cm2. This easy ultrasonographic volumetric technique makes it possible to perform a semi-quantitative assessment of thyroid volume and to differentiate diffuse goiter from normal-sized thyroids.